Adverse pregnancy outcomes and long-term risk of maternal renal disease: a systematic review. (13th November 2019) - Barrett, P; McCarthy, F P; Kublickiene, K; Cormican, S; Judge, C; Evans, M; Kublickas, M; Perry, I J; Stenvinkel, P; Khashan, A S
Abstract: Background: Little is known about the long-term risk of renal disease following adverse pregnancy outcomes, such as hypertensive disorders of pregnancy (HDP), gestational diabetes (GDM) or preterm delivery. We aimed to investigate associations between adverse pregnancy outcomes and maternal chronic kidney disease (CKD) and end-stage kidney disease (ESKD), by synthesising results of relevant studies. Methods: A systematic search of PubMed, EMBASE and Web of Science was done up to July 2018. Case-control and cohort studies were eligible for inclusion if they provided original effect estimates for associations between adverse pregnancy outcomes (HDP, GDM, preterm) and maternal renal disease (primary outcomes: CKD, ESKD; secondary outcomes: renal hospitalisation, renal mortality). Two independent reviewers extracted data and assessed risk of bias. Random effects meta-analyses were conducted to determine pooled adjusted odds ratio (AOR) and 95% confidence interval (95%CI) for each association. Results: Of 5, 120 studies retrieved, 21 studies met inclusion criteria (4, 483, 847 participants). HDP was associated with increased odds of ESKD (AOR 6.58, 95%CI 4.06-10.65), CKD (AOR 2.08, 95%CI 1.06-4.10), renal hospitalisation (AOR 2.29, 95%CI 1.42-3.71). The magnitude of association was dependent on HDP subtype: AOR for preeclampsia and ESKD was 4.87 (95%CI 3.01-7.87); gestational hypertension and ESKD was 3.65 (95%CI 2.34-5.67); other HDP (including chronic hypertension) and ESKD was 14.67 (95%CI 3.21-66.97). Preterm delivery was associated with increased odds of ESKD (AOR 2.16, 95%CI 1.64-2.85). GDM was associated with increased odds of CKD among black women (AOR 1.78, 95%CI 1.18-2.70), but not Caucasian women (AOR 0.81, 95%CI 0.58-1.13) Conclusions: Women who experience adverse pregnancy outcomes have increased odds of renal disease, especially after HDP. Risk stratification and preventive interventions may be needed to reduce the risk of clinically significant renal disease in mothers. Key messages: This is the first study to summarise the long-term risk of renal disease among women who experience a range of adverse pregnancy outcomes. Women who experience hypertensive disorders in pregnancy, preterm delivery, or gestational diabetes are at increased odds of renal disease.